2015
DOI: 10.1016/j.jpainsymman.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Medication and Monitoring in Palliative Sedation Therapy: A Systematic Review and Quality Assessment of Published Guidelines

Abstract: The published guidelines on PST vary considerably regarding their quality and content on drugs and monitoring. Given the need for clear guidance regarding PST in patients at the end of life, this comparative analysis may serve as a starting point for further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 24 publications
(98 reference statements)
3
61
0
4
Order By: Relevance
“…Based on the evaluation results of the AGREE II instrument, lower quality scores are observed in the domains of ‘stakeholder involvement’, ‘applicability’ and ‘editorial independence’. This result is similar to findings by other authors appraising guidelines with the original AGREE instrument or updated AGREE II version . Regarding the ‘stakeholder involvement’, it requires a clear definition of the target users, a demonstration that the views and preferences of the target population have been sought and documentation that the guideline development group includes all relevant professional groups .…”
Section: Discussionsupporting
confidence: 83%
“…Based on the evaluation results of the AGREE II instrument, lower quality scores are observed in the domains of ‘stakeholder involvement’, ‘applicability’ and ‘editorial independence’. This result is similar to findings by other authors appraising guidelines with the original AGREE instrument or updated AGREE II version . Regarding the ‘stakeholder involvement’, it requires a clear definition of the target users, a demonstration that the views and preferences of the target population have been sought and documentation that the guideline development group includes all relevant professional groups .…”
Section: Discussionsupporting
confidence: 83%
“…Several authors already pointed at a lack of accepted terminology and a consistent framework which makes it difficult to describe different PS practices [25, 34]. Even different frameworks that should assist as guidance vary considerably in content and quality [35]. The parent study to this analysis [14] showed that a considerable percentage of institutional representatives were not aware of the EAPC framework [2] or its German translation [36].…”
Section: Discussionmentioning
confidence: 99%
“…Former studies have considered scientifically derived assessment tools or theoretical guidelines and recommendations, but no investigation has yet looked at those documents which were specifically developed and used in clinical every-day practice (27,29,38).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, these (inter-)national guidelines, position statements, and the related literature on PS recommendations have been investigated, in order to evaluate its content and methodological quality (26,27). Gurschick et al compared several published guidelines on PS from different medical societies and found variances considering definitions of the practice, indications for its use, continuation of life-prolonging therapies, medications used, and timing/prognosis throughout these guidelines (28).…”
Section: Introductionmentioning
confidence: 99%